Isosorbide modified polyethylene glycol terephthalate-1, 4-cyclohexanedimethanol and preparation method of isosorbide modified polyethylene glycol terephthalate-1, 4-cyclohexanedimethanol

The polyethylene terephthalate-1,4-cyclohexanedimethanol ester modified by isosorbide solves the problem of insufficient heat resistance and oxygen barrier properties of PETG materials, and achieves high glass transition temperature and oxygen barrier properties, suitable for heat-resistant and oxygen-sensitive material packaging.

CN119119440AInactive Publication Date: 2024-12-13BEIJING KERUI HECHUANG CONSULTING CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411380983.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The heat resistance and oxygen barrier properties of PETG materials are insufficient, cannot withstand hot water cleaning and pasteurization, and are limited in use in areas where high oxygen barrier properties are required.

Method used

Isosorbitol ethylene terephthalate-1,4-cyclohexanedimethanol ester was modified, and titanium and antimony catalysts were introduced through esterification and polycondensation reaction to improve the glass transformation of copolyesters. Transition temperature and oxygen barrier properties.

Benefits of technology

The glass transition temperature and oxygen barrier properties of PETG materials are significantly improved, allowing them to withstand hot water cleaning and pasteurization, and are used in oxygen-sensitive material packaging while maintaining high strength, transparency and easy processability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119440A_ABST
    Figure CN119119440A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyester preparation, and provides isosorbide modified polyethylene glycol terephthalate-1, 4-cyclohexanedimethanol ester and a preparation method of the isosorbide modified polyethylene glycol terephthalate-1, 4-cyclohexanedimethanol ester. The preparation method comprises the following steps: mixing terephthalic acid, ethylene glycol, 1, 4-cyclohexanedimethanol, isosorbide and a compound catalyst, and sequentially carrying out an esterification reaction and a condensation polymerization reaction to obtain the isosorbide modified polyethylene terephthalate-1, 4-cyclohexanedimethanol. By introducing the isosorbide, the heat resistance and oxygen barrier property of the copolyester are greatly improved, the problems of poor heat resistance and poor oxygen barrier property of the existing PETG material are solved, and the obtained copolyester inherits good mechanical properties, transparency and processability of the PETG material and has a wide application prospect. In addition, the preparation method provided by the invention is simple, mild in condition, stable in product performance and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester preparation, and in particular to isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester and a preparation method thereof. Background Art

[0002] Polyester is a type of polymer formed by the condensation of polyacids and polyols. It is classified into two categories according to its chemical structure: semi-rigid polyester and fully rigid aromatic polyester. It has the advantages of high modulus, light weight, and excellent thermal stability. Combined with its excellent properties of low cost, simple process, and strong practicality, it is widely used in fibers, resins, films and other fields.

[0003] Semi-crystalline thermoplastic polyesters are widely used in daily life and engineering construction. They can be found in everything from carbonated beverages and water bottles to clothing and fibers. Polyethylene terephthalate (PET) is one of the most commonly used semi-crystalline thermoplastic polyesters. It is made by esterification and polycondensation of terephthalic acid and ethylene glycol. Although some polyesters, such as polypropylene terephthalate (PCT), polybutylene terephthalate (PDT), and polyethylene naphthalate (PEN), have been commercially successful, they cannot compete with PET in terms of cost performance. Due to the excellent cost performance of PET, researchers have been looking for ways to improve its performance through copolymerization of third monomers, chemical grafting, and blending modification. For example, in order to address the problem that PET's molecular chain is relatively regular, which makes it easy to crystallize and become brittle, a third monomer, 1,4-cyclohexanedimethanol (CHDM), was introduced to synthesize a polyester with better performance, PETG. PETG is made of terephthalic acid (PTA), ethylene glycol (EG) and 1,4-cyclohexanedimethanol (CHDM) by ester exchange. With the increase of CHDM content in the copolymer, the molecular structure becomes more disordered, which makes the melting point of PETG drop, the glass transition temperature rise and the crystallization ability decrease, forming an amorphous polymer polyester material. Since PETG and other materials have strong complementary advantages and disadvantages, it can be blended with engineering plastics such as PC and ABS in actual use.

[0004] However, the addition of CHDM did not substantially improve the rigidity of the molecular chain, resulting in a decrease in the glass transition temperature (T g ) is still low and cannot withstand hot water cleaning and pasteurization, which increases the risk of bacterial and microbial growth during reuse and makes it unusable as a heat-resistant material, such as a magnetron sputtering substrate. At the same time, PETG's oxygen barrier property is also poor and cannot be used in areas that require a high degree of oxygen barrier properties, such as beer, liquor and other volatile beverage packaging.

[0005] In summary, how to effectively improve the heat resistance and oxygen barrier properties of PETG materials is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0006] In view of this, the present invention provides an isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester and a preparation method thereof. The present invention uses isosorbide terephthalate-1,4-cyclohexanedimethanol ester (PETG) for modification, and the heat resistance and oxygen barrier properties of the obtained copolyester are greatly improved, and at the same time, it has excellent mechanical properties, high transparency and good processability; and isosorbide is a renewable bio-based monomer with low cost.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A method for preparing isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester comprises the following steps:

[0009] Terephthalic acid, ethylene glycol, 1,4-cyclohexanedimethanol, isosorbide and a composite catalyst are mixed, and esterification reaction and polycondensation reaction are carried out in sequence to obtain the isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester; the composite catalyst includes a titanium catalyst and an antimony catalyst.

[0010] Preferably, the molar ratio of terephthalic acid to ethylene glycol is 1:0.4-0.6; the molar ratio of terephthalic acid to 1,4-cyclohexanedimethanol is 1:(0-0.4), and the molar amount of 1,4-cyclohexanedimethanol is not 0; the molar ratio of terephthalic acid to isosorbide is 1:(0-0.4), and the molar amount of isosorbide is not 0.

[0011] Preferably, the titanium-based catalyst includes a titanate catalyst.

[0012] Preferably, the titanate catalyst includes one or more of tetrabutyl titanate, tetraethyl titanate and tetraisopropyl titanate.

[0013] Preferably, the antimony-based catalyst includes one or more of antimony oxide, antimony glycol and antimony acetate.

[0014] Preferably, the mass ratio of the titanium-based catalyst to the antimony-based catalyst is 1:(0.3-1).

[0015] Preferably, the mass of the composite catalyst is 0.1% to 0.3% of the total mass of the terephthalic acid, ethylene glycol, 1,4-cyclohexanedimethanol and isosorbide.

[0016] Preferably, the temperature of the esterification reaction is 230-270° C., the absolute pressure is 100-200 kPa, and the reaction time is 1-2 h.

[0017] Preferably, the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction carried out in sequence; the temperature of the pre-polycondensation reaction is 260-290°C, and the absolute pressure is 3-6kPa; the temperature of the final polycondensation reaction is 260-290°C, and the absolute pressure is 100-200Pa, and the total time of the pre-polycondensation reaction and the final polycondensation reaction is 2-3h.

[0018] The present invention also provides isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester prepared by the preparation method described in the above scheme.

[0019] The present invention provides a method for preparing isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester, comprising the following steps: mixing terephthalic acid (TPA), ethylene glycol (EG), 1,4-cyclohexanedimethanol (CHDM), isosorbide (ISB) and a composite catalyst, and sequentially performing esterification reaction and polycondensation reaction to obtain the isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester (denoted as PETGI copolyester); the composite catalyst comprises a titanium catalyst and an antimony catalyst. Isosorbide has a unique chiral center and a rigid structure. The present invention introduces ISB into the polyester main chain, which can increase the rigidity of the molecular chain and restrict the movement of the molecular chain, thereby increasing the glass transition temperature (T g ); at the same time, the irregular furan ring structure in ISB also increases the randomness of the molecular chain, making it difficult to crystallize, avoiding the problem of easy crystallization and brittleness. Therefore, the present invention adopts TPA, EG, CHDM and ISB four monomers for copolymerization, and the glass transition temperature and oxygen barrier property of the obtained PETGI copolyester are greatly improved. It can withstand hot water cleaning and pasteurization, can be used as a heat-resistant material, and can also package oxygen-sensitive materials; at the same time, the PETGI copolyester of the present invention also inherits all the advantages of PETG materials (such as high strength, high transparency, easy processability, etc.). The results of the embodiment show that when ISB is not used for modification, the glass transition temperature of PETG is 80.48°C. After adding ISB monomer for modification, the glass transition temperature of the obtained PETGI copolyester is significantly improved, among which The glass transition temperature can reach 94.91°C; from the DSC data, PETGI copolyesters are all amorphous polymers; through the barrier performance test, it can be seen that the introduction of isosorbide can greatly improve the oxygen barrier property of PETGI copolyester; and the PETGI copolyester prepared by the present invention also has excellent tensile strength and elongation at break, excellent mechanical properties, good stability and high transparency.

[0020] In addition, ISB is a renewable bio-based monomer that can avoid dependence on petroleum resources, is more environmentally friendly and has lower costs.

[0021] Furthermore, the present invention uses a composite catalyst to catalyze the reaction, which can make the reaction more stable, the reaction temperature lower, and the conditions milder.

[0022] In summary, the preparation method provided by the present invention is simple to operate, can achieve one-step synthesis, has mild conditions, and is low in cost. The obtained PETGI copolyester product has good heat resistance and barrier properties and high performance stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The NMR spectra of the copolyesters prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are as follows: Figure 1 (a) is a schematic diagram of the structure of PETGI copolymer, (b) is the H-NMR spectrum of the copolyester, and (c) is an enlarged view of the dotted area in (b);

[0024] Figure 2 The actual photos of the copolyesters prepared in Comparative Example 1, Example 1, Comparative Example 2 and Example 3, wherein from left to right are Comparative Example 1, Example 1, Comparative Example 2 and Example 3;

[0025] Figure 3 The DSC test results of the copolyesters obtained in Example 1, Example 3 and Comparative Examples 1-2 are shown;

[0026] Figure 4 The barrier properties test results of the copolyesters obtained in Examples 1 to 3 and Comparative Examples 1 to 2, wherein (a) is the oxygen permeability test result, and (b) is the water vapor permeability test result. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester, comprising the following steps:

[0028] Terephthalic acid, ethylene glycol, 1,4-cyclohexanedimethanol, isosorbide and a composite catalyst are mixed, and esterification reaction and polycondensation reaction are carried out in sequence to obtain the isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester; the composite catalyst includes a titanium catalyst and an antimony catalyst.

[0029] In the present invention, the molar ratio of terephthalic acid to ethylene glycol is preferably 1:0.4-0.6, more preferably 1:0.6; in a specific embodiment of the present invention, since ethylene glycol is volatile, it is preferably fed in an excess of 50-60%. In the present invention, the molar ratio of terephthalic acid and 1,4-cyclohexanedimethanol is preferably 1:(0-0.4), and the molar amount of 1,4-cyclohexanedimethanol is not 0; in a specific embodiment of the present invention, the molar ratio of terephthalic acid and 1,4-cyclohexanedimethanol is preferably 1:(0.1-0.3), specifically 1:0.1, 1:0.15, 1:0.2, 1:0.25 or 1:0.3; the molar ratio of terephthalic acid and isosorbide is preferably 1:(0-0.4), and the molar amount of isosorbide is not 0; in a specific embodiment of the present invention, the molar ratio of terephthalic acid and isosorbide is preferably 1:(0.1-0.3), specifically 1:0.1, 1:0.15, 1:0.2, 1:0.25 or 1:0.3.

[0030] In the present invention, the isosorbide is a white solid powder with a melting point of 56-62° C., a boiling point of 372° C., strong water absorption, and a structural formula as shown in Formula I.

[0031]

[0032] As shown in Formula I, the isosorbide molecule is composed of two furan condensed rings connected at 120 °, wherein, there is a secondary hydroxyl group on the 2nd and 5th positions, the secondary hydroxyl group on the 2nd position is exo-type, and the secondary hydroxyl group on the 5th position is endo-type, this special configuration causes the hydrogen atom in the secondary hydroxyl group on the 5th position to form a hydrogen bond with the oxygen atom on the adjacent oxygen-containing heterocycle, increases steric hindrance, causes the reactivity of the endo-OH on the 5th position to decrease, and the secondary hydroxyl group on the 2nd position extends out of the ring, which also means that the two-OH activities inside the isosorbide are different. Simultaneously, as can be seen from the molecular structural formula of isosorbide, it is a chiral molecule, and the molecular structure has very large rigidity. The present invention introduces the structure of isosorbide in copolyester, can greatly improve the glass transition temperature and oxygen barrier of copolyester, and ensures its mechanical properties simultaneously.

[0033] In the present invention, the titanium catalyst preferably includes a titanate catalyst; the titanate catalyst preferably includes one or more of tetrabutyl titanate, tetraethyl titanate and tetraisopropyl titanate; the antimony catalyst preferably includes one or more of antimony oxide, antimony glycol and antimony acetate; the mass ratio of the titanium catalyst to the antimony catalyst is preferably 1: (0.3-1), more preferably 1: 0.4-0.7; in a specific embodiment of the present invention, the composite catalyst is preferably composed of tetrabutyl titanate and antimony glycol, and the mass ratio of tetrabutyl titanate to antimony glycol is preferably 3: 2; the mass of the composite catalyst is preferably 0.1% to 0.3% of the total mass of terephthalic acid, ethylene glycol, 1,4-cyclohexanedimethanol and isosorbide, more preferably 0.15% to 0.3%. In the present invention, the titanium catalyst has high activity, violent reaction, easy hydrolysis, easy side reaction during polymerization, and the polymer obtained by the reaction is yellow; the antimony catalyst has a mild reaction, but the polymer obtained by the reaction is dark in color. The invention aims at the characteristic that two hydroxyl groups in isosorbide have low activity, cooperates with two catalysts to carry out catalytic reaction, can improve reaction activity, and obtain high-quality products under mild conditions.

[0034] In the present invention, the temperature of the esterification reaction is preferably 230-270°C, more preferably 235-250°C; the absolute pressure of the esterification reaction is preferably 100-200 kPa, more preferably 150-190 kPa; the reaction time of the esterification reaction is preferably 1-2 h; in a specific embodiment of the present invention, the esterification rate of the reaction solution is preferably detected, and the esterification is considered to be completed when the esterification rate reaches 97%.

[0035] In the present invention, the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction which are carried out in sequence; the temperature of the pre-polycondensation reaction is preferably 260-290°C, more preferably 275-285°C, and the absolute pressure of the pre-polycondensation reaction is preferably 3-6 kPa, more preferably 4-5 kPa. In a specific embodiment of the present invention, when no more large amounts of small molecules evaporate and the tower top temperature drops, the pre-polycondensation reaction is considered to be finished.

[0036] In the present invention, the temperature of the final polycondensation reaction is preferably 260-290°C, more preferably 275-285°C. In a specific embodiment of the present invention, the temperature of the final polycondensation reaction is the same as the temperature of the preliminary polycondensation reaction; the absolute pressure of the final polycondensation reaction is preferably 100-200Pa, more preferably 100-150Pa, and the total time of the preliminary polycondensation reaction and the final polycondensation reaction is preferably 2-3h. In a specific embodiment of the present invention, it is preferred to monitor the data (torque) of the real-time resistance conversion current of the reactor stirring paddle, and the reaction ends when the current stabilizes and no longer rises.

[0037] In the present invention, the esterification reaction, the preliminary polycondensation reaction and the final polycondensation reaction are preferably carried out under nitrogen protection, and the reaction pressure is controlled by the amount of nitrogen introduced.

[0038] In a specific embodiment of the present invention, it is preferred to first fill the reactor with nitrogen for replacement once, then add terephthalic acid, ethylene glycol, 1,4-cyclohexanedimethanol, isosorbide and a composite catalyst into the reactor, replace it with nitrogen for 3 times, then heat it to 150°C, start stirring and continue to heat it to the temperature of the esterification reaction, then fill it with nitrogen to the pressure required for the esterification reaction, heat it after the esterification reaction and adjust the pressure to carry out a pre-polycondensation reaction, and adjust the pressure after the pre-polycondensation reaction to carry out a final polycondensation reaction.

[0039] The present invention also provides isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester (referred to as PETGI copolyester) prepared by the preparation method described in the above scheme. In the present invention, the structural formula of the PETGI copolyester is shown in Formula II:

[0040]

[0041] In the present invention, the intrinsic viscosity of the PETGI copolyester is 0.65 to 0.90 dL / g, more preferably 0.6750 to 0.8863 dL / g, and the viscosity average molecular weight is preferably 18000 to 26500, more preferably 18920 to 26374. The PETGI copolyester provided by the present invention has good heat resistance and oxygen barrier properties, high mechanical properties, high transparency, good processability, and has broad application prospects.

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] Synthesis of PETGI copolyester: 830g PTA, 294g EG, 201.6g CHDM, 102.2g ISB and 0.43g composite catalyst (tetrabutyl titanate: antimony glycol = 6:4) were added to the reactor, replaced with nitrogen for 3 times, heated to 150°C, stirred, heated to 235°C, and filled with nitrogen to make the pressure in the reactor reach 190kPa. The pressure in the reactor was maintained at 190kPa for esterification. When the reaction time was 2h, the esterification rate reached 97%, and the esterification was completed. After the esterification reaction was completed, the temperature was raised to 275°C, and a pre-polycondensation reaction was carried out at an absolute pressure of 4kPa. After that, the temperature was maintained at 275°C, and a final polycondensation reaction was carried out at an absolute pressure of 100Pa. The reaction was completed until the current was stable and no longer increased, and PETGI copolyester was obtained. The total reaction time of pre-polycondensation and final polycondensation was 180min; the obtained PETGI copolyester was recorded as

[0045] Example 2

[0046] Synthesis of PETGI copolyester: 830g PTA, 294g EG, 151.2g CHDM, 153.3g ISB and 0.43g composite catalyst (tetrabutyl titanate: antimony glycol = 6:4) were added to the reactor, replaced with nitrogen for 3 times, heated to 150°C, stirred, heated to 235°C, filled with nitrogen to make the pressure in the reactor reach 190kPa, and maintained the pressure in the reactor at 190kPa for esterification. When the reaction time was 2h, the esterification rate reached 97%, and the esterification was completed. After the esterification reaction was completed, the temperature was raised to 275°C, and a pre-polycondensation reaction was carried out at an absolute pressure of 4kPa. After that, the temperature was maintained at 275°C, and a final polycondensation reaction was carried out at an absolute pressure of 100Pa. The reaction was completed until the current was stable and no longer increased, and PETGI copolyester was obtained. The total reaction time of pre-polycondensation and final polycondensation was 175min; the obtained PETGI copolyester was recorded as

[0047] Example 3

[0048] Synthesis of PETGI copolyester: 830g PTA, 294g EG, 100.8g CHDM, 204.4g ISB and 0.43g composite catalyst (tetrabutyl titanate: antimony glycol = 6:4) were added to the reactor, nitrogen was filled and replaced 3 times, the temperature was raised to 150°C, stirring was started, the temperature was raised to 235°C, nitrogen was filled to make the pressure in the reactor reach 190kPa, and the pressure in the reactor was maintained at 190kPa for esterification reaction. When the reaction time was 2h, the esterification rate reached 97%, and the esterification was completed. After the esterification reaction was completed, the temperature was raised to 275°C, and a pre-polycondensation reaction was carried out at an absolute pressure of 4kPa. After that, the temperature was maintained at 275°C, and a final polycondensation reaction was carried out at an absolute pressure of 100Pa. After the reaction, the current was stable and no longer rose, which was the end of the reaction, and PETGI copolyester was obtained. The total reaction time of pre-polycondensation and final polycondensation was 172min; the obtained PETGI copolyester was recorded as

[0049] Comparative Example 1

[0050] 830g PTA, 294g EG, 302.4g CHDM, 0g ISB and 0.43g composite catalyst (tetrabutyl titanate: ethylene glycol antimony = 6:4) were added to the reactor, nitrogen was filled and replaced 3 times, the temperature was raised to 150°C, stirring was started, the temperature was raised to 235°C, nitrogen was filled to make the pressure in the reactor reach 190kPa, and the pressure in the reactor was maintained at 190kPa for esterification reaction. The esterification reaction was completed when the esterification rate reached 97%. After the esterification reaction was completed, the temperature was raised to 275°C, and a pre-condensation reaction was carried out under an absolute pressure of 4kPa. After that, the temperature was maintained at 275°C, and a final condensation reaction was carried out under an absolute pressure of 100Pa. The reaction was completed when the current was stable and no longer increased, and a copolyester was obtained; the obtained PETGI copolyester was recorded as

[0051] Comparative Example 2

[0052] 830g PTA, 294g EG, 0g CHDM, 306.6g ISB and 0.43g composite catalyst (tetrabutyl titanate: ethylene glycol antimony = 6:4) were added to the reactor, nitrogen was replaced 3 times, the temperature was raised to 150°C, stirring was started, the temperature was raised to 235°C, nitrogen was charged to make the pressure in the reactor reach 190kPa, and the pressure in the reactor was maintained at 190kPa for esterification reaction. The esterification reaction was completed when the esterification rate reached 97%. After the esterification reaction was completed, the temperature was raised to 275°C, and a pre-polycondensation reaction was carried out under an absolute pressure of 4kPa. After that, the temperature was maintained at 275°C, and a final polycondensation reaction was carried out under an absolute pressure of 100Pa. The reaction was completed when the current was stable and no longer increased, and a copolyester was obtained; the obtained PETGI copolyester was recorded as

[0053] Comparative Example 3

[0054] The other conditions were the same as those in Example 1, except that the composite catalyst was replaced by a single catalyst, and all the catalysts used were tetrabutyl titanate. The esterification reaction time was 3 h, and the total time for the pre-polycondensation reaction and the final polycondensation reaction was 5.5 h.

[0055] Comparative Example 4

[0056] The other conditions were the same as those in Example 1, except that the composite catalyst was replaced by a single catalyst, and all the catalysts used were ethylene glycol antimony. The esterification reaction time was 3.5 h, and the total time for the pre-polycondensation reaction and the final polycondensation reaction was 6 h.

[0057] Performance Test:

[0058] 1. MRI test

[0059] The copolyesters prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to NMR tests. The results are as follows: Figure 1 As shown, Figure 1 (a) is a schematic diagram of the structure of PETGI copolymer, (b) is the H-NMR spectrum of the copolyester, and (c) is an enlarged view of the dotted area in (b).

[0060] The molar ratio of each unit in the copolyester was calculated according to the NMR test results. The results are shown in Table 1.

[0061] Table 1 Molar ratio of each unit in copolyester

[0062]

[0063] 2. Product appearance

[0064] Figure 2 The following are photos of the copolyesters prepared in Comparative Example 1, Example 1, Comparative Example 2 and Example 3, where from left to right they are Comparative Example 1, Example 1, Comparative Example 2 and Example 3. Figure 2 It can be seen that the copolyester material prepared in Example 1 of the present invention has better transparency. Similar to Comparative Example 1, the amount of ISB used in Example 3 is relatively large, and the prepared copolyester is slightly yellowish, which is caused by the particularity of ISB.

[0065] 2. Intrinsic viscosity ([η]) and viscosity-average molecular weight (M η )test

[0066] The intrinsic viscosity ([η]) and viscosity average molecular weight (M) of the copolyesters obtained in Examples 1 to 2 and Comparative Examples 1 to 2 were measured by the method in GB / T14190-2017. η ) were tested, and the results are shown in Table 2.

[0067] Table 2 Intrinsic viscosity ([η]) and viscosity average molecular weight (M) of the copolyesters obtained in Examples 1 to 3 and Comparative Examples 1 to 4 η )

[0068] project [η] / dL / g <![CDATA[M η ]]> Comparative Example 1 0.8732 25899 Example 1 0.8863 26374 Example 2 0.7452 21347 Example 3 0.6750 18920 Comparative Example 2 0.5651 15234 Comparative Example 3 0.6639 18541 Comparative Example 4 0.6542 18212

[0069] According to the data in Table 2, it can be seen that the intrinsic viscosity ([η]) and viscosity average molecular weight (M) of the PETGI prepared in Examples 1 to 3 of the present invention are η ) is not much different from the PETG copolyester prepared in Comparative Example 1, and inherits the excellent processability of PETG copolyester; Comparative Examples 3 to 4 use a single catalyst to prepare copolyester, the reaction time is long, and the molecular weight of the obtained copolyester is low.

[0070] 3. Mechanical properties test

[0071] The tensile strength and elongation at break of the copolyesters obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the results are shown in Table 3.

[0072] Table 3 Test results of tensile strength and elongation at break of Examples 1 to 3 and Comparative Examples 1 to 2

[0073] project Tensile strength(MPa) Elongation at break (%) Comparative Example 1 42.52 235.93 Example 1 48.71 227.6 Example 2 49.90 220.5 Example 3 52.72 156.23 Comparative Example 2 28.98 4.56

[0074] According to the data in Table 3, it can be seen that the tensile strength and elongation at break of the PETGI copolyester prepared in Examples 1 to 3 of the present invention are both high. Although the elongation at break of the copolyester decreases slightly with the increase of ISB, the overall mechanical properties are high, inheriting the advantages of good mechanical properties of PETG; while CHDM is omitted in Comparative Example 2, the mechanical properties of the obtained copolyester are greatly reduced.

[0075] 4. Thermal performance test

[0076] The thermal properties of the copolyesters obtained in Examples 3 to 6 were tested using a differential scanning calorimeter (DSC model: Discovery 2500), and the test conditions were as follows: the N2 flow rate was 40 mL / min, the sample was first heated from 0°C to 200°C at a heating rate of 10°C / min, stayed at 250°C for 3 min to eliminate the thermal history, and then cooled to -40°C at a rate of 10°C / min.

[0077] The DSC test results of the copolyesters obtained in Examples 1, 3 and Comparative Examples 1 to 2 are as follows: Figure 3 As shown. Figure 3It can be seen from the data that with the increase of the proportion of isosorbide, the glass transition temperature of the obtained copolyester gradually increases. When no isosorbide is added, the obtained copolyester is actually PETG, and its glass transition temperature is only 80.48°C. When the molar ratio of PTA and ISB is 1:0.4, the glass transition temperature of the obtained copolyester reaches 106.43°C, indicating that with the increase of ISB dosage, the heat resistance of the copolyester can be significantly improved; combined with Figure 3 As can be seen from the data in Table 2, the use of isosorbide in Examples 2 and 3 of the present invention to modify PETG copolyester can significantly improve its heat resistance while ensuring the mechanical properties of the copolyester. In addition, it can also be seen from the DSC data that the PETGI copolyesters prepared by the present invention are all amorphous polymers.

[0078] 4. Barrier performance test

[0079] The copolyesters of Examples 1 to 3 and Comparative Examples 1 to 2 were prepared into films by melt pressing. The oxygen barrier properties of the obtained copolyester films were tested at 23°C using GTR-701M. The thickness of the films was 5 mm and the surface area was 38.48 cm 2 The water barrier properties of the film were tested using WVTR-9003 at 23°C and 70% RH. The test results are as follows: Figure 4 As shown, (a) is the oxygen permeability test result, and (b) is the water vapor permeability test result.

[0080] according to Figure 4 It can be seen that with the increase of ISB content, the oxygen permeability of the obtained copolyester film gradually decreases, and the water vapor permeability gradually increases, indicating that the oxygen barrier property gradually increases, and the water vapor barrier property slightly decreases. From the comprehensive test results of oxygen barrier property and water vapor barrier property, it can be seen that the copolyesters prepared in Examples 1 to 3 of the present invention have both excellent oxygen barrier property and water vapor barrier property.

[0081] It can be seen from the results of the above embodiments that the present invention greatly improves the heat resistance and oxygen barrier properties of the copolyester by introducing isosorbide, which can solve the problems of poor heat resistance and poor oxygen barrier properties of the current PETG material, and the copolyester obtained by the present invention inherits the good mechanical properties, transparency and processability of the PETG material, and has broad application prospects.

[0082] In summary, the present invention uses isosorbide to modify the PETG material, and the beneficial effects are as follows:

[0083] (1) The synthesis method of the PETGI copolyester of the present invention is simple, can be prepared in one step, has a low reaction temperature and mild reaction conditions.

[0084] (2) The PETGI copolyester prepared by the present invention has a large increase in glass transition temperature, good performance stability, can withstand hot water cleaning and pasteurization, and can be used as a heat-resistant material.

[0085] (3) The PETGI copolyester prepared by the present invention has significantly improved oxygen barrier properties and can be used to package oxygen-sensitive materials.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester, characterized in that: The following steps are involved: Terephthalic acid, ethylene glycol, 1,4-cyclohexanedimethanol, isosorbide and a composite catalyst are mixed, and esterification reaction and polycondensation reaction are carried out in sequence to obtain the isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol ester; the composite catalyst includes a titanium catalyst and an antimony catalyst.

2. The preparation method according to claim 1, characterized in that: The molar ratio of terephthalic acid to ethylene glycol is 1:0.4-0.6; the molar ratio of terephthalic acid to 1,4-cyclohexanedimethanol is 1:(0-0.4), and the molar amount of 1,4-cyclohexanedimethanol is not 0; the molar ratio of terephthalic acid to isosorbide is 1:(0-0.4), and the molar amount of isosorbide is not 0.

3. The preparation method according to claim 1, characterized in that: The titanium-based catalyst includes a titanate-based catalyst.

4. The preparation method according to claim 3, characterized in that: The titanate catalyst includes one or more of tetrabutyl titanate, tetraethyl titanate and tetraisopropyl titanate.

5. The preparation method according to claim 1, characterized in that: The antimony-based catalyst includes one or more of antimony oxide, antimony glycol and antimony acetate.

6. The preparation method according to any one of claims 1, 3, 4 and 5, characterized in that: The mass ratio of the titanium-based catalyst to the antimony-based catalyst is 1:(0.3-1).

7. The preparation method according to any one of claims 1, 3, 4 and 5, characterized in that: The mass of the composite catalyst is 0.1% to 0.3% of the total mass of the terephthalic acid, ethylene glycol, 1,4-cyclohexanedimethanol and isosorbide.

8. The preparation method according to claim 1, characterized in that: The temperature of the esterification reaction is 230-270° C., the absolute pressure is 100-200 kPa, and the reaction time is 1-2 hours.

9. The preparation method according to claim 1, characterized in that: The polycondensation reaction comprises a pre-polycondensation reaction and a final polycondensation reaction which are carried out in sequence; the temperature of the pre-polycondensation reaction is 260-290° C., and the absolute pressure is 3-6 kPa; the temperature of the final polycondensation reaction is 260-290° C., and the absolute pressure is 100-200 Pa; and the total time of the pre-polycondensation reaction and the final polycondensation reaction is 2-3 h.

10. Isosorbide-modified polyethylene terephthalate-1,4-cyclohexanedimethanol prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Low-molecular soluble chelating collector as well as preparation method and application thereof

    CN121319347A

  • Low molecular weight soluble chelating collectors, their preparation methods and applications

    CN121319347B